BEHAVIOR OF LAYING HENS WITH DIFFERENT MONOCHROMATIC LIGHT SOURCES - DA SILVA, Gabriela Fagundes; TAVARES, Bartira de Oliveira; PEREIRA, Danilo Florentino (Revista Brasileira de Engenharia de Biossistemas, 2012)
Both wavelengths as the light intensity influence the physiology of birds, interfering with animal welfare and productivity. This research aimed to monitor the behavior of laying hens reared in enriched environment lit by LED lamps in four different colors, and analyze how the different light spectra affected the behavior. The experiment was conducted in a shed on a reduced scale distorted, which were built four identical compartments. In each compartment lighting of a different color (blue, red, green and white), a video camera to monitor the birds, a nest and roost, and the floor was covered with wood shavings bed was installed. Sixty-four hens were divided in two experiments, in groups of two birds in each compartment, a total of four replicates of seven days for each experiment. In the first experiment we sought to analyze the behavior of the birds in an enriched environment, subjected to only one of the four lighting treatments. In the second experiment, birds were given free to choose between the compartments where there was the preference of the birds for lighting treatments. The results showed that the eating behavior was influenced by the treatments, and the birds ate more when exposed to green light compared to blue light. No other significant differences were observed in other behaviors analyzed. In the preference test, there was no preference for any of the birds tested lighting treatments.